Soviet economic growth : conditions and perspectives - Joint Committee on Slavic Studies (U.S.); Bergson, Abram (Evanston, Ill. : Row, Peterson, 1953)
This book is about national income of the soviet union and the structure of it's economy.
"Sets forth in ... revised form the proceedings of a conference held at Arden House, Harriman, N.Y., May 23-25, 1952 ... organized under the sponsorship of the Joint Committee on Slavic Studies of the American Council of Learned Societies and the Social Science Research Council."
Includes bibliographical footnotes and index.
oo 12/09/2018
Loans
Keywords: Labor supply; Soviet Union